2019
DOI: 10.4102/jomped.v3i1.63
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metals in some selected medicinal plants growing within the University of Ibadan Campus

Abstract: Background: Medicinal plants are a potent source of therapeutic molecules that heal various diseases in the world.Aim: The aim of this study was to evaluate heavy metal concentrations in the leaves of some selected medicinal plants in selected locations.Setting: The leaves of Azadirachta indica, Magnifera indica and Newbouldia laevis were collected from the botanical garden, roadside and residential area in the University of Ibadan and were authenticated at the Forest Herbarium Ibadan. The samples were thoroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
1
4
Order By: Relevance
“…The comparison of this permissible limit with the results obtained indicated that the concentration of chromium was above the permissible limit except in PL1, PL2, and YF3. However, the chromium concentrations of 0.57 to 2.04 ppm of herbs in similar studies from Kenya [29] and 0.73 to 4.79 ppm in some selected medicinal plants growing within the University of Ibadan Campus, Nigeria [58] were above the results obtained in this finding. The concentrations of zinc ranged from 26.65 to 48.61 ppm medicinal herbs.…”
Section: Resultscontrasting
confidence: 54%
“…The comparison of this permissible limit with the results obtained indicated that the concentration of chromium was above the permissible limit except in PL1, PL2, and YF3. However, the chromium concentrations of 0.57 to 2.04 ppm of herbs in similar studies from Kenya [29] and 0.73 to 4.79 ppm in some selected medicinal plants growing within the University of Ibadan Campus, Nigeria [58] were above the results obtained in this finding. The concentrations of zinc ranged from 26.65 to 48.61 ppm medicinal herbs.…”
Section: Resultscontrasting
confidence: 54%
“…The levels of Cd recorded in this study were lower compared to similar studies earlier reported, (1.66 ppm) in ten important folk therapeutic plants, Peshawar, Pakistan (Jabeen et al, 2010), (14.05 µg/g) in some selected medicinal plants, Kumasi, Ghana (Kofi et al, 2013) and (0.36 ppm)in some selected medicinal plants, Ibadan, Nigeria (Rufai et al, 2019), but in line with values reported by Kishan et al, (2014). Chromium is important in carbohydrate metabolism and also functions in cholesterol and protein synthesis (Kishan et al, 2014), but chronic exposure of chromium may result in nose irritations, skinrash, stomach upset, bleeds, kidney, liver and lung damage (Zayed and Terry, 2003;Baye and Hymete, 2013).…”
Section: Resultscontrasting
confidence: 73%
“…Similarly, it has been confirmed that the deficiency of nickel in the human body results in liver disorder (Khan et al, 2008). The levels of Ni in this present study were higher than (0.88 mg/kg) and (0.113 ppm) reported in medicinal plants from India (Kishan et al, 2014), Borno, Nigeria (Adamu et al, 2016), and below detectable limit from Ibadan, Nigeria (Rufai et al, 2019) respectively. Lead is a non-essential element, exposure of lead beyond the permissible limits or long term use of contaminated plants may result in chronic nephritis, headache, colic, anemia, convulsions, brain damage and central nervous system (CNS) disorders (Tong et al, 2000;Klaassen, 2001;Kishan et al, 2014).…”
Section: Bajopas Volume 13 Number 1 June 2020contrasting
confidence: 73%
See 2 more Smart Citations